2016
DOI: 10.1016/j.anr.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Programs on eGFR, Depression, and Quality of Life among Patients with Chronic Kidney Disease: A Meta-Analysis

Abstract: Self-management programs of patients with chronic kidney disease can improve the depression and mental quality of life. Aside from providing more objective evidence-based results, this study provides a reference for clinical health care personnel who tend to patients with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
3
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 25 publications
7
52
3
9
Order By: Relevance
“…Both systematic reviews identified similar studies of which five were randomised controlled trials (RCTs) (Byrne et al, 2011;Campbell et al, 2008;Chen et al, 2011;Flesher et al, 2011;Williams et al, 2012). The other three systematic reviews (Lee et al, 2016;Lin et al, 2017;Lopez-Vargas et al, 2016) included only RCTs of CKD self-management interventions in either pre-dialysis patients or in those already receiving dialysis. Lee et al (2016) included two RCTs involving pre-dialysis patients (Campbell et al, 2008;Chen et al, 2011), both of which were also reported by and Welch et al (2014) in their systematic reviews.…”
Section: Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both systematic reviews identified similar studies of which five were randomised controlled trials (RCTs) (Byrne et al, 2011;Campbell et al, 2008;Chen et al, 2011;Flesher et al, 2011;Williams et al, 2012). The other three systematic reviews (Lee et al, 2016;Lin et al, 2017;Lopez-Vargas et al, 2016) included only RCTs of CKD self-management interventions in either pre-dialysis patients or in those already receiving dialysis. Lee et al (2016) included two RCTs involving pre-dialysis patients (Campbell et al, 2008;Chen et al, 2011), both of which were also reported by and Welch et al (2014) in their systematic reviews.…”
Section: Reviewsmentioning
confidence: 99%
“…Thus, improving people's kidney disease-related knowledge is important for early symptoms, taking prescribed medications, and adhering to other management strategies. Patient education has been shown to be extremely important in improving CKD knowledge in five recent systematic reviews in CKD self-management Lee et al, 2016;Lin et al, 2017;Lopez-Vargas et al, 2016;Welch et al, 2014). A more detailed examination of these systematic reviews occurs in section 2.5.…”
Section: 41mentioning
confidence: 99%
See 3 more Smart Citations